INDONESIA’S INTEREST IN BILATERAL CURRENCY SWAP ARRANGEMENT (BCSA) WITH SOUTH KOREA - Egita Marina Silalahi; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study analyzes Indonesia's interest in Bilateral Currency Swap Arrangement (BCSA) cooperation with South Korea. The signing of the BCSA is an implementation of the agreement between Indonesia and South Korea to conduct bilateral swap in 2013. In general, swap transactions are expected to protect the central bank or international economic activities from the risk of currency fluctuations. For Indonesia, transactions with local currencies can have a good impact, because they can reduce dependence on the US Dollar. Bank Indonesia signed the first BCSA agreement on 06 March 2014 with a validity period of 3 years. This cooperation has also been extended 2 times, namely in 2017 and 2020. This cooperation is expected to ensure the settlement of trade transactions in local currency between the two countries, even in the event of a global crisis or uncertainty. This research uses qualitative methods, with data collection techniques through literature studies sourced from books, journals, articles, and websites. This research uses the perspective of liberaslism and the theory of international cooperation. The result of this paper is Indonesia's interest in BCSA, one of which is for the settlement of trade transactions and also to support the financial market deepening program, all of which can refer to economic resilience and stability. Bank Indonesia also seeks to maximize the implementation of the BCSA agreement by issuing PBI number 18/7/PBI/2016 and also PBI number 24/2/PBI/2022 which contains transaction implementation to sanctions during transaction implementation which are expected to reduce the use of US dollars, and can maintain economic stability and currency stability. Keywords: Currency swap, exchange rate, financial stability, international cooperation.